Two-Year Outcomes after Left Main Coronary Artery Percutaneous Coronary Intervention in Patients Presenting with Acute Coronary Syndrome - Si-Da Jia; Yi Yao; Ying Song; Xiao-Fang Tang; Xue-Yan Zhao; Run-Lin Gao; Yue-Jin Yang; Bo Xu; Zhan Gao; Jin-Qing Yuan (Journal of Interventional Cardiology)
Objectives. We aim to evaluate long-term outcomes after left main coronary artery (LMCA) percutaneous coronary intervention (PCI) in patients presenting with acute coronary syndrome (ACS). Background. PCI of the LMCA has been an acceptable revascularization strategy in stable coronary artery disease. However, limited studies on long-term clinical outcomes of LMCA PCI in ACS patients are available. Methods. A total of 6429 consecutive patients with ACS undergoing PCI in Fuwai Hospital in 2013 were enrolled. Patients are divided into LMCA group and Non-LMCA group according to whether the target lesion was located in LMCA. Prognosis impact on 2-year major adverse cardiovascular and cerebrovascular events (MACCE) is analyzed. Results. 155 (2.4%) patients had target lesion in LMCA, while 6274 (97.6%) patients belong to the non-LMCA group. Compared with non-LMCA patients, LMCA patients have generally more comorbidities and worse baseline conditions. Two-year follow-up reveals that LMCA patients have significantly higher rate of cardiac death (2.6% vs. 0.7%, p=0.034), myocardial infarction (7.1% vs. 1.8%, p<0.001), in-stent thrombosis (4.5% vs. 0.8%, p<0.001), and stroke (7.1% vs. 6.4%, p=0.025). After adjusting for confounding factors, LMCA remains independently associated with higher 2-year myocardial infarction rate (HR = 2.585, 95% CI = 1.243–5.347, p=0.011). Conclusion. LMCA-targeted PCI is an independent risk factor for 2-year myocardial infarction in ACS patients.